2021
DOI: 10.1200/jco.2021.39.15_suppl.tps9137
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of PD-1 inhibitor JTX-4014 alone and in combination with vopratelimab, an ICOS agonist, in biomarker-selected subjects with metastatic NSCLC after one prior platinum-containing regimen (SELECT).

Abstract: TPS9137 Background: Immune checkpoint inhibitors have led to durable remissions for some patients with advanced malignancies, including NSCLC; however, only a minority of patients benefit. The field of oncology is addressing this via the development of novel therapies, combinations and identification of biomarkers to select patients most likely to derive clinical benefit. ICOS, a novel therapeutic target, is a costimulatory molecule upregulated on activated T cells. Vopratelimab is an investigational IgG1 ICO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The first-in-human phase I/II ICONIC trial (NCT0290422) revealed that this antibody boosts the activation and proliferation of primed CD4 T effector cells and leads to improved clinical outcomes in patients treated with this antibody both as a monotherapy and in combination with the anti-PD-1 inhibitor nivolumab [ 210 , 211 ]. Following promising results from this phase I clinical trial with no adverse safety and tolerability concerns, it is currently being analyzed in the SELECT phase II trial (NCT04549025) in combination with another PD-1 inhibitor (pimivalimab, JTX-4014) in NSCLC patients [ 212 ].…”
Section: Behind the Steps Of Lag-3 Towards The Clinicmentioning
confidence: 99%
“…The first-in-human phase I/II ICONIC trial (NCT0290422) revealed that this antibody boosts the activation and proliferation of primed CD4 T effector cells and leads to improved clinical outcomes in patients treated with this antibody both as a monotherapy and in combination with the anti-PD-1 inhibitor nivolumab [ 210 , 211 ]. Following promising results from this phase I clinical trial with no adverse safety and tolerability concerns, it is currently being analyzed in the SELECT phase II trial (NCT04549025) in combination with another PD-1 inhibitor (pimivalimab, JTX-4014) in NSCLC patients [ 212 ].…”
Section: Behind the Steps Of Lag-3 Towards The Clinicmentioning
confidence: 99%
“…Agonistic antibodies are currently being administered either alone or in combination with immunotherapy, including immune checkpoint inhibitors as well as with chemotherapy [26 && ]. However, an ICOS agonist feladilimab has been halted in a phase 2 clinical trial in the combination of ipilimumab in patients with NSCLC due to unsatisfactory clinical benefit; this SELECT trial investigated PD-1 inhibitor JTX-4014 in combination with vopratelimab, an ICOS agonist, in metastatic NSCLC after one prior regimen (NCT04549025) [27].…”
Section: Inducible T Cell Costimulatormentioning
confidence: 99%
“…However, an ICOS agonist feladilimab has been halted in a phase 2 clinical trial in the combination of ipilimumab in patients with NSCLC due to unsatisfactory clinical benefit; this SELECT trial investigated PD-1 inhibitor JTX-4014 in combination with vopratelimab, an ICOS agonist, in metastatic NSCLC after one prior regimen (NCT04549025) [27].…”
Section: Supply Of Costimulatory Signalsmentioning
confidence: 99%